ANALISIS PEMENUHAN HAK RESTITUSI TINDAK PIDANA PERSETUBUHAN TERHADAP ANAK DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK (Studi Kasus: Putusan Nomor 116/Pid.Sus-Anak/2018/Pn.Kng) - Mochamad Farhan Sutansyaddaafi; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2020)
The formation of Law No. 35 of 2014 concerning Child Protection has not yet had an impact on reducing the level of violence against children, especially cases of sexual violence. The Witness and Victim Protection Agency says there has been an increase in the number of cases of sexual violence against children that have occurred since 2016 from an initial 25 cases, increasing to 206 cases in 2018, the number continues to increase every year. The state is obliged to provide legal protection to its citizens, one of the forms presented by the state is restitution. However, in the effort to fulfill restitution, obstacles often occur, one of which occurs in Decision Number 116 / Pid.Sus-Anak / 2018 / Pn.Kng where victims of sexual violence do not receive restitution as mandated by Article 71D of the Child Protection Act. So that the problem arises how the fulfillment of the right to restitution of the crime of intercourse against children, the research method used is normative legal research for academic purposes supported by the results of the interview. The results of the analysis in this study are that there are still many obstacles such as unequal knowledge of law enforcement regarding the rights of victims. Law enforcers should pay more attention to matters relating to the rights of victims, because victims as the injured party for all things done by the perpetrators are entitled to receive restitution in accordance with the rights granted by law.